Penerapan Metode Five Modulus Dalam Mengkompresi File Dokumen (PDF) Pengembangan Bahan Ajar - Sitohang, Norenta (Jurnal Sains Informatika Terapan, 2023)
PDF files are one of the document files that are classified as having sufficient size larger than other document files. Currently, the use of applications as information is increasing commonly used. But there is a problem that is often encountered, namely the need for a safe place great for storage. Therefore, compression is needed to reduce the size of the application data. Data compression is a process of converting a set of data into a form of code to reduce the need for data storage space. The Five Modulus method is wrong a data compression algorithm. To find out the results of the compression process is done through the ratio compression and space saving. The results to be known, the compression ratio and space saving. According to the test results The tests that were carried out show that the data that originally had a larger size can be very well compressed on the application of the Five Modulus method in compressing document files (PDF).